Ethical problems experienced by nurse managers in the pandemic of COVID-19 in a university hospital - Simone Graziele Silva Cunha; Sérgio Deodato; Maria José Menezes Brito (Universidade Federal do Ceará, 2023)
Objective: to understand the ethical problems experienced by nurse managers in the context of the COVID-19 pandemic. Methods: qualitative study, conducted with 19 nurse managers. The inclusion criteria were nurses who had held a management position for at least six months, and the exclusion criteria were those who held an assistance position. Data were collected through individual interviews with a semi-structured script and document analysis and analyzed using Content Analysis. Results: the ethical problems were related to duplicity and lack of information about norms and routines; lack of patient flow; routine changes without communication with the nurse coordinators; absenteeism and presenteeism of the nursing team; refusal of reassignment by technicians; nursing professionals who chose to work in the COVID-19 sector and earn additional unhealthy salary and those who did not choose due to fear of disease; and conflicts arising from the patient. Conclusion: the analysis revealed situations marked by ethical problems that compromise the dynamics of work and the quality of care. Contributions to practice: understanding ethical problems contributes to the promotion of improvements in planning, intervention, and preparation of professionals to deal with conflicting issues experienced in hospital management.